Technological change and employment: were Ricardo and Marx right? - Piva, Mariacristina; Vivarelli, Marco (Bonn, 2017)
"The aim of this paper is twofold. On the one hand, the economic insights about the employment impact of technological change are disentangled starting from the classical economists to nowadays theoretical and empirical analyses. On the other hand, an empirical test is provided; in particular, longitudinal data – covering manufacturing and service sectors over the 1998-2011 period for 11 European countries – are used to run GMM-SYS and LSDVC estimates. Two are the main results: 1) a significant labour-friendly impact of R&D expenditures (mainly related to product innovation) is found; yet, this positive employment effect appears to be entirely due to the medium-and high-tech sectors, while no effect can be detected in the low-tech industries; 2) capital formation is found to be negatively related to employment; this outcome points to a possible labour-saving effect due to the embodied technological change incorporated in gross investment (mainly related to process innovation)."